2011
DOI: 10.1111/j.1365-3024.2011.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of β‐glucan on innate immunity and resistance of Lutjanus guttatus to an experimental infection of dactylogyrid monogeneans

Abstract: The present study investigated the effect of β-1,3/1,6-glucan on growth, haematology, innate immunity and resistance against dactylogyrids on the spotted rose snapper (Lutjanus guttatus). Fish were fed during 5 weeks with commercial diet (control group) and same diet supplemented with three levels of β-glucans (0·05%, 0·1% and 0·5%/kg feed). The results showed that at concentrations of 0·05% and 0·1%, fish growth was enhanced, and in weeks 2 and 4, an increase in cellular responses such as percentage of monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
(58 reference statements)
3
15
0
5
Order By: Relevance
“…Results from this research show a general improvement in some hematological and immunological parameters after β-1,3/1,6 glucan intake, especially during weeks 3 and 4. However, some hematological parameters (Ht and RBC) showed opposed results decreasing over experimental time, agreeing with other studies (Del Rio-Zaragoza et al, 2011) which also reported high leucocytes values using same β-1,3/1,6 glucan concentration (0.05%) supplemented to red snapper Lutjanus guttatus commercial diet, and also a decrease in Ht and RBC values after the first treatment week.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Results from this research show a general improvement in some hematological and immunological parameters after β-1,3/1,6 glucan intake, especially during weeks 3 and 4. However, some hematological parameters (Ht and RBC) showed opposed results decreasing over experimental time, agreeing with other studies (Del Rio-Zaragoza et al, 2011) which also reported high leucocytes values using same β-1,3/1,6 glucan concentration (0.05%) supplemented to red snapper Lutjanus guttatus commercial diet, and also a decrease in Ht and RBC values after the first treatment week.…”
Section: Discussionsupporting
confidence: 80%
“…No significant variation on total serum protein values during the experiment on any different diet groups were observed, which is similar to that reported in other species (Dicentrarchus labrax, L. guttatus) fed with β-1,3/1,6 glucan supplemented diets using similar concentrations (SitjÀ-Bobadilla & Pérez-Sánchez, 1999;Bagni et al, 2005;Del Rio-Zaragoza et al, 2011). No difference (P > 0.05) on glucose levels between treated and control fish were observed, suggesting a proper response from fish to biological modifiers like β-1,3/1,6 glucans.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The ensuing diseases generate great economic losses during culture; therefore, the use of immunostimulants has increased in the aquaculture industry [21], with the prebiotic β-1,3/1,6-glucan being one of the most frequently used [31]. Under present experimental conditions, the incorporation of this prebiotic in balanced feeds designed for A. tropicus did not result in an improvement of the somatic growth parameters (body weight, length, SGR, FCR, and K).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on different fish species, such as Atlantic salmon (Salmo salar, Linnaeus 1758) [18], rainbow trout (Oncorhynchus mykiss, Walbaum 1792) [15,19,20], spotted rose snapper (Lutjanus guttatus, Steindachner 1869) [21], common carp (Cyprinus carpio, Linnaeus 1758) [16,22,23], roho labeo (Labeo rohita, Hamilton 1822) [13,24], gilthead sea bream (Sparus aurata Linnaeus 1758) [25], sea bass (Dicentrarchus labrax, Linnaeus 1758) [26,27], Nile tilapia (Oreochromis niloticus, Linnaeus 1758) [28], silver seabream (Pagrus auratus, Forster 1801) [12], large yellow croaker (Pseudosciaena crocea, Richardson 184) [29], and southern bluefin tuna (Thunnus maccoyii, Castelnau 1872) [30] have reported that β-glucans act by modulating different parameters of the immune response and increasing resistance to diseases [8,12]. Therefore, the objective of the present study was to determine the effect of different oral doses of β-1,3/1,6-glucan on growth, survival, digestive enzymatic activity, and the expression of several genes associated with the immune system and the intestinal barrier function in juveniles of the tropical gar (A. tropicus).…”
Section: Introductionmentioning
confidence: 99%